Reliability growth structural components gas-turbine engine to casehardening - Кулик, М.С.; Ляшенко, Б.А.; Мірненко, В.І.; Тамаргазін, О.А. (Proceedings of National Aviation University (archive), 2010)
In this article we examine the question of reliability raise of compressor blades on the martempering basis of a complex of thermomechanical properties of titanium alloys multipurpose vacuum-plasma (PVD) covers.